(untitled) (Iraqi National Journal of Earth Science (INJES), 2025)
1), and the A-CN-K plot, all indicate a low to moderate chemically weathered source area. Palaeoclimatic information can be provided using the plot of the SiO2 versus (Al2O3+Na2O + K2O) indicating that the deposition of Injana sandstones has occurred under fluctuated climate between arid to semi-arid.]]>